FUNGSI PENDIDIKAN BAHASA DAN SASTRA INDONESIA DALAM MEMBANGUN KEPRIBADIAN BANGSA - NURBAYA, SITI (FOUNDASIA, 2005)
Language and literature education can be utilized as a medium nf devcloping a nation's personality. In the context of culture, a language is part of the means to maintain the social order which is universal in nature. Therefore, a language can influence a culture. The relationship between a language as a means of communication and a culture in the sense of creation, feeling, and work can be established ac a medium qf developing humanistic values. Literary works containing humanistic values can serve as a medium of transforming a nation's personality values.